1996
DOI: 10.1021/ja9603766
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of Alkali Metals to Oligosaccharides Dictates Fragmentation Behavior in Matrix Assisted Laser Desorption Ionization/Fourier Transform Mass Spectrometry

Abstract: A correlation is found between the fragment ion yield and the degree of branching for oligosaccharides analyzed by matrix assisted laser desorption ionization/Fourier transform mass spectrometry (MALDI/FTMS). The most branched oligosaccharides produced the least amount of fragment ion. Another relationship is found between the size of the alkali metal ion and the yields of fragment ions. The smallest alkali metal ion produced the greatest amount of fragment ions. The presence of the quasimolecular ion is depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
221
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(230 citation statements)
references
References 68 publications
(109 reference statements)
8
221
1
Order By: Relevance
“…The utility of mass spectral analysis of gangliosides by MALDI-FTMS has been demonstrated, but its application has been hampered by extensive metastable fragmentation when standard MALDI sources are employed [27,28,30,40,41], and derivatization, e.g., permethylation, is often necessary to stabilize the more highly labile species sufficiently to enable MS analysis. In the case of homogeneous standards, metastable fragmentation can be used to verify the details of the ganglioside structures, but for heterogenous samples like those typically extracted from biological tissues, extensive fragmentation during the analysis makes determination of the composition of the ganglioside mixtures extremely difficult or impossible.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utility of mass spectral analysis of gangliosides by MALDI-FTMS has been demonstrated, but its application has been hampered by extensive metastable fragmentation when standard MALDI sources are employed [27,28,30,40,41], and derivatization, e.g., permethylation, is often necessary to stabilize the more highly labile species sufficiently to enable MS analysis. In the case of homogeneous standards, metastable fragmentation can be used to verify the details of the ganglioside structures, but for heterogenous samples like those typically extracted from biological tissues, extensive fragmentation during the analysis makes determination of the composition of the ganglioside mixtures extremely difficult or impossible.…”
Section: Resultsmentioning
confidence: 99%
“…With both Electrospray and MALDI mass spectrometry, the loss of sialic acid residues is the predominant fragmentation pathway. This property is particularly important for MALDI-FTMS where the relatively long time between ionization and detection (0.3-30 s depending on the resolution desired and the pumping efficiency of the specific vacuum system) allows unimolecular metastable fragmentation reactions to go to completion [28,30,32]. However, some methods have been developed to partially stabilize the gangliosides on desorption.…”
mentioning
confidence: 99%
“…As glycans can be easily isolated and purified, the ISD and pMS 3 -sequencing approaches were also employed to characterize thoroughly the structures of both native [43,[54][55][56][57][58][59][60] and permethylated glycans [61][62][63][64][65][66], allowing unambiguous discrimination of isobaric species. In ref.…”
Section: Maldi-isd and Ptmsmentioning
confidence: 99%
“…Low-energy activation methods, such as collisional activated dissociation (CAD) and infrared multiphoton dissociation (IRMPD), applied to protonated oligosaccharides results in predominantly glycosidic cleavages. However, oligosaccharides ionized with alkali, alkaline earth, and transition metals often fragment to yield more cross-ring cleavages compared to their protonated counterparts [11][12][13][14]. Although fragmentation of neutral oligosaccharides in negative-ion mode is not as frequently examined, it has been demonstrated that native, neutral oligosaccharide anions produce abundant C-type glycosidic cleavages and A-type cross-ring cleavages in CAD, as opposed to B-and Y-type glycosidic cleavages, which are commonly observed for oligosaccharide cations (Domon and Costello nomenclature [15]) [16 -19].…”
mentioning
confidence: 99%